Popular culture, crime and social control - Deflem, Mathieu (Emerald, 2010)
This volume contains contributions on the theme of popular culture, crime, and social control. The chapters in this volume tease out various criminologically relevant issues, pertaining to crime/deviance and/or the control thereof, on the basis of an analysis of various aspects and manifestations of popular culture, including music, movies, television, paintings, sculptures, photographs, cartoons, and the internet-based audio-visual materials that are presently available. Thematically diverse within the province of criminology, the chapters in this book are not restricted in terms of theoretical approach and methodological orientation. Using a variety of methodological and theoretical perspectives, the volume is diverse in addressing dimensions of popular culture in relation to important criminological questions.
Description based on print version record.
Keywords: Popular culture.; Crime.; Social control.; Sociology & anthropology.; Crime & criminology.; Social Science -- Sociology -- General.; Social Science -- Popular Culture.; Social Science -- Criminology.; elektronické knihy; electronic books